2011
DOI: 10.1186/1471-244x-11-140
|View full text |Cite
|
Sign up to set email alerts
|

Long term life dissatisfaction and subsequent major depressive disorder and poor mental health

Abstract: BackgroundPoor mental health, especially due to depression, is one of the main public health problems. Early indicators of poor mental health in general population are needed. This study examined the relationship between long-term life dissatisfaction and subsequent mental health, including major depressive disorder.MethodHealth questionnaires were sent to a randomly selected population-based sample in 1998 and repeated in 1999 and 2001. In 2005, a clinically studied sub-sample (n = 330) was composed of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 30 publications
5
49
0
Order By: Relevance
“…These data are in line with the results obtained in other studies (e.g. Mueller, Bridges & Goddard, 2011;Rissanen et al, 2011). As described by Fröjd et al (2008) and Chen and Li (2000), a significant relationship between School Performance (SP) and Depressive Symptomatology was found.…”
Section: Responsibility Of the Organizing Committee Of The Conferencesupporting
confidence: 82%
See 1 more Smart Citation
“…These data are in line with the results obtained in other studies (e.g. Mueller, Bridges & Goddard, 2011;Rissanen et al, 2011). As described by Fröjd et al (2008) and Chen and Li (2000), a significant relationship between School Performance (SP) and Depressive Symptomatology was found.…”
Section: Responsibility Of the Organizing Committee Of The Conferencesupporting
confidence: 82%
“…As for recreational activities, a longitudinal study of a sample of adolescents revealed that leisure activities, including physical activity, and depressed mood co-vary inversely during adolescence (Birkeland, Torsheim & Wold, 2009). A study by Rissanen et al (2011), which examined the relationship between satisfaction with life and depressive symptoms in a sample of the general population, concluded that the two variables are significantly related, and that poor satisfaction predicts worse depressive symptomatology and worse mental health.…”
Section: Responsibility Of the Organizing Committee Of The Conferencementioning
confidence: 99%
“…John et al, 2014), and suicidality (Koivumaa-Honkanen et al, 2001;Rissanen et al, 2011). Rates of asthma, arthritis, diabetes, and heart disease are disproportionately greater among individuals who report life dissatisfaction (Ampon et al, 2005).…”
Section: Page 6 Of 43mentioning
confidence: 96%
“…Other authors have studied more specifically the relationship between some fields of the PF, such as school performance (Chen & Li, 2000;Fröjd et al, 2008), the quality of the relationships with the family Pinheiro et al, 2013) and friends (Greca & Harrison, 2005) and recreational activities (Gledhill & Garralda, 2010), and satisfaction functioning in various areas of life (Koivumaa-Honkanen et al, 2001;Rissanen et al, 2011) and depressive symptoms in adolescence. This investigation the PF global and its various areas was studied, finding that the depressive symptoms are associated with PF global and with satisfaction with functioning, as with almost all dimensions of PF (relationships with family and friends and existence of recreational activities).…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with life also seems to be associated with subjective well-being, relating negatively with depression (Koivumaa-Honkanen et al, 2001). In a sample of 330 adults, the longitudinal study of Rissanen et al (2011) revealed that dissatisfaction was strongly related to the development of depression. Sheeber, Hops, Alpert, Davis and Andrews (1997) reported that depressive symptoms in adolescents are related with the quality of their family relationships.…”
Section: Introductionmentioning
confidence: 99%